Quality in services of the Food and Nutrition Unit - UAN in times of Covid-19 (Research, Society and Development, 2021)
Introduction: With the spread of the Sars-CoV-2 virus and the world in a state of pandemic, the food industry needed to reinvent itself and adopt new ways to serve customers and consumers. The Food and Nutrition Units (UANs) that serve diners did not have their activities suspended because they are an essential service, they had to adapt to the new scenario and make internal, theoretical and environmental changes. General objective: Based on a bibliographic study, this article aims to discuss the importance of adopting Good Practice standards and important aspects involved in the management of good quality in food and nutrition, as well as how they influence the whole process even in a pandemic period, as they avoid contamination and reduce the risk of foodborne illnesses (DTAs). Results and Discussion: The exercise of good practices increases the quality of food and the nutritional safety of consumers, together with reducing expenses, increasing the organization and generation of products, motivating employees and strengthening the customer-company bond. Conclusion: This paper also emphasizes how essential the role of the nutritionist is for the success of activities in FNUs, in addition to structural, sanitary and economic advantages and summarizes the new recommendations attributed to the nutritionist, justified by the need to fight the pandemic, in a context isolation and social distance.